2020
DOI: 10.1021/acs.jafc.0c01679
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of 5-Hydroxymethylfurfural into 6-(Hydroxymethyl)pyridin-3-ol: A Pathway for the Formation of Pyridin-3-ols in Honey and Model Systems

Abstract: The formation of 6-(hydroxymethyl)pyridin-3-ol by ring expansion of 5-(hydroxymethyl)furfural (HMF) in the presence of ammonia-producing compounds was studied to determine the routes of formation of pyridin-3-ols in foods. 6-(Hydroxymethyl)pyridin-3-ol was produced from HMF in model systems, mostly at neutral pH values, as a function of reaction times and temperature and with an activation energy (E a ) of 74 ± 3 kJ/mol, which was higher than that of HMF disappearance (43 ± 4 kJ/mol). A reaction pathway is pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…During the thermal processing of food, large amounts of α‐DCs and the abovementioned hazardous substances are generated. Although much research has indicated that α‐DCs are useful indicators of the degree of heat treatment (Hidalgo et al., 2020; Nikolov & Yaylayan, 2011; Zhao et al., 2021), few attempts have been made to develop indexes for acrylamide, furan, ALEs, and AGEs using the corresponding α‐DCs as proxies. Above all, it is necessary to accurately determine the contents of α‐DCs in foods to clarify their relationships with these hazardous substances.…”
Section: Introductionmentioning
confidence: 99%
“…During the thermal processing of food, large amounts of α‐DCs and the abovementioned hazardous substances are generated. Although much research has indicated that α‐DCs are useful indicators of the degree of heat treatment (Hidalgo et al., 2020; Nikolov & Yaylayan, 2011; Zhao et al., 2021), few attempts have been made to develop indexes for acrylamide, furan, ALEs, and AGEs using the corresponding α‐DCs as proxies. Above all, it is necessary to accurately determine the contents of α‐DCs in foods to clarify their relationships with these hazardous substances.…”
Section: Introductionmentioning
confidence: 99%